The genome of Magnolia hypoleuca provides a new insight into cold tolerance and the evolutionary position of magnoliids - Zhou, Luojing; Hou, Feixia; Wang, Li; Zhang, Lingyu; Wang, Yalan; Yin, Yanpeng; Pei, Jin; Peng, Cheng; Qin, Xiaobo; Gao, Jihai (Frontiers in Plant Science, 2023)
Magnolia hypoleuca Sieb. & Zucc, a member of the Magnoliaceae of magnoliids, is one of the most economically valuable, phylogenetic and ornamental tree species in Eastern China. Here, the 1.64 Gb chromosome-level assembly covers 96.64% of the genome which is anchored to 19 chromosomes, with a contig N50 value of 1.71 Mb and 33,873 protein-coding genes was predicted. Phylogenetic analyses between M. hypoleuca and other 10 representative angiosperms suggested that magnoliids were placed as a sister group to the eudicots, rather than sister to monocots or both monocots and eudicots. In addition, the relative timing of the whole-genome duplication (WGD) events about 115.32 Mya for magnoliid plants. M. hypoleuca was found to have a common ancestor with M. officinalis approximately 23.4 MYA, and the climate change of OMT (Oligocene-Miocene transition) is the main reason for the divergence of M. hypoleuca and M. officinalis, which was along with the division of Japanese islands. Moreover, the TPS gene expansion observed in M. hypoleuca might contribute to the enhancement of flower fragrance. Tandem and proximal duplicates of younger age that have been preserved have experienced more rapid sequence divergence and a more clustered distribution on chromosomes contributing to fragrance accumulation, especially phenylpropanoid, monoterpenes and sesquiterpenes and cold tolerance. The stronger selective pressure drived the evolution of tandem and proximal duplicates toward plant self-defense and adaptation. The reference M. hypoleuca genome will provide insights into the evolutionary process of M. hypoleuca and the relationships between the magnoliids with monocots and eudicots, and enable us to delve into the fragrance and cold tolerance produced by M. hypoleuca and provide more robust and deep insight of how the Magnoliales evolved and diversified.